2018
DOI: 10.1111/desc.12747
|View full text |Cite
|
Sign up to set email alerts
|

Remapping the cognitive and neural profiles of children who struggle at school

Abstract: Our understanding of learning difficulties largely comes from children with specific diagnoses or individuals selected from community/clinical samples according to strict inclusion criteria. Applying strict exclusionary criteria overemphasizes within group homogeneity and between group differences, and fails to capture comorbidity. Here, we identify cognitive profiles in a large heterogeneous sample of struggling learners, using unsupervised machine learning in the form of an artificial neural network. Childre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 100 publications
(125 reference statements)
2
53
0
Order By: Relevance
“…Emerging first in adult psychiatry (Cuthbert & Insel, 2013; Morris & Cuthbert, 2012), transdiagnostic approaches focus on identifying underlying symptom dimensions that likely span multiple supposed categories (e.g., Astle, Bathelt, The CALM Team, & Holmes, 2019; Bathelt, Holmes, et al, 2018; Bryant, Guy, The CALM Team, & Holmes, 2020; Hawkins, Gathercole, Astle, The CALM Team, & Holmes, 2016; Holmes et al, 2019; Siugzdaite et al, 2020). Within developmental science there are good examples of researchers cutting across hitherto unquestioned diagnostic boundaries in order to identify cognitive symptoms that underpin learning, but they remain relatively rare (e.g., Astle et al, 2019; Casey, Oliveri, & Insel, 2014; Hulme & Snowling, 2009; Peng & Fuchs, 2016; Sonuga-Barke & Coghill, 2014; Zhao & Castellanos, 2016). A review of a transdiagnostic approach is well beyond the scope of the current article, but suffice it to say, contemporary developmental science needs larger and more diverse samples.…”
Section: Moving Beyond the Core-deficit Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging first in adult psychiatry (Cuthbert & Insel, 2013; Morris & Cuthbert, 2012), transdiagnostic approaches focus on identifying underlying symptom dimensions that likely span multiple supposed categories (e.g., Astle, Bathelt, The CALM Team, & Holmes, 2019; Bathelt, Holmes, et al, 2018; Bryant, Guy, The CALM Team, & Holmes, 2020; Hawkins, Gathercole, Astle, The CALM Team, & Holmes, 2016; Holmes et al, 2019; Siugzdaite et al, 2020). Within developmental science there are good examples of researchers cutting across hitherto unquestioned diagnostic boundaries in order to identify cognitive symptoms that underpin learning, but they remain relatively rare (e.g., Astle et al, 2019; Casey, Oliveri, & Insel, 2014; Hulme & Snowling, 2009; Peng & Fuchs, 2016; Sonuga-Barke & Coghill, 2014; Zhao & Castellanos, 2016). A review of a transdiagnostic approach is well beyond the scope of the current article, but suffice it to say, contemporary developmental science needs larger and more diverse samples.…”
Section: Moving Beyond the Core-deficit Hypothesismentioning
confidence: 99%
“…But relative to SEM-based approaches and network analysis, machine-learning applications remain underdeveloped. Although popular in other areas of science with similar challenges, these methods have yet to gain much traction within the study of developmental differences (but see Astle et al, 2019). These algorithms are highly flexible, and the resulting models can easily accommodate nonlinear relationships, make predictions about unseen data, be combined with simulations, incorporate different data types, and open the way to tools for testing generalization, such as cross-validation.…”
Section: Moving Beyond the Core-deficit Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…And yet these individual differences are often overlooked, and current approaches broadly take univariate statistical approaches, which are unable to identify individual cognitive profiles of performance on the basis of rich multivariate data. Contemporary multivariate analysis methods offer a radical rethink of training and associated transfer (Astle, Bathelt, The CALM Team, & Holmes, 2019; Bathelt, Holmes, & Astle, on behalf of the CALM Team, 2018) by focusing on training-related changes in task relationships.…”
Section: Individual Differences: Personalizing Trainingmentioning
confidence: 99%
“…The search for a unique causal factor in reading disability/dyslexia has largely been replaced by recognition that the problem is multifactorial, involving a range of risk and protective factors at genetic, neural, cognitive and environmental levels, with the weighting of each of these varying across individuals (Pennington, 2006;Pennington et al, 2012;Vandermosten et al, 2016). Continuing the current practice of diagnosing dyslexia on the basis of the presence of one or more of a long list of cognitive and behavioural symptoms, common to most poor readers, is no longer appropriate and may explain why Astle et al (2019) found little relationship between diagnoses of 530 children struggling at school and their cognitive profiles.…”
Section: Diagnosing Dyslexiamentioning
confidence: 99%